FORMULASI DAN KARAKTERISASI MIKROKAPSUL MINYAK TOKOFERIL ASETAT - Fardesia, Diah
Tocopheryl acetate is a derivative form of vitamin E that can also reduce skin damage caused by UV light by acting as an antioxidant. This substance is unstable when exposed to air, so to increase its stability, tocopheryl acetate oil is formulated in the form of microcapsules. This study aims to develop a formula containing tocopheryl acetate oil by complex coacervation method and evaluate the characteristics of the formed microcapsules. The optimization of the microcapsule formula was carried out using chitosan and acasia gum as coating polymer and sodium tripolyphosphate as crosslinking agent. The results showed that the optimum volume ratio to form an emulsion of tocopheryl acetate oil in acasia gum was 1.5:10; while the optimum weight ratio of chitosan and acasia gum is 2:9. The homogenization process was carried out at 7000 rpm for 7 minutes. The organoleptic characteristic of microcapsules was in the form of cream colored powder with a size of 1.066 ?m ± 0.101 and a polydispersity index of 0.406 ?m ± 0.024. The antioxidant activity of the obtained tocopheryl acetate microcapsules was not significantly different from the pure tocopheryl acetate. On storage for 35 days at room temperature and 40°C, encapsulation efficiency of microcapsule decreased by 9.73% and 19.45%, respectively. The microencapsulation process carried out on tocopheryl acetate oil has not been able to improve its stability well.